PERAN KOMISI PEMILIHAN UMUM KOTA JAKARTA TIMUR DALAM MENINGKATKAN PARTISIPASI PEMILIH MASYARAKAT KOTA JAKARTA TIMUR PADA PEMILU PRESIDEN TAHUN 2019 - Johannes Situmeang (2023)
This study aims to explain the strategy carried out by the East Jakarta Election Comission in order to increase voter participation in the 2019 Presidential and Vice-Presidential election. The method used in this research is descriptive qualitative using primary data sources and secondary data. The author uses four analytical stages according to Miles & Huberman including: data collection, data reduction, data presentation, and drawing conclusions. The final results in this study indicate that the East Jakarta Election Comission strategy in increasing voter turnout in East Jakarta in the 2019 Presidential and Vice Presidential election has been well implemented, the Election Comission carries out outreach activities to all levels of society assisted by a team of democracy volunteers, PPK, PPS, Political Parties, Non-Governmental Organizations and Community Organizations thus experiencing an increase. The percentage of participation in the 2019 Presidential and Vice-Presidential election which was held in East Jakarta was at 80.46%, this number exceeded the national target set by The General Election Commission of the Republic of Indonesia, which was 77.5%. The strategy used by the East Jakarta Election Comission to increase voter participation uses Chandler's strategy formulation indicators which are divided into three strategies, including: Formulation and long-term goals, selection of actions, and resource allocation. Implementation of the strategy is carried out through voter education socialization activities, optimizing the use of digital media, and increasing human resources. Keywords: KPU, Strategy, 2019 Presidential and Vice Presidential Election